Application of Brain Based Learning Model to Reduce Mathematics Anxiety and Improve Student Learning Outcomes - Irawati, Tri Novita; Winarsih, Dinda Tria; MT., A. Mujib (Journal of Education and Learning Mathematics Research (JELMaR), 2025)
Mathematic anxiety and low student learning outcomes are problems that need special attention, especially in the field of mathematics learning. The purpose of this study is to reduce students' mathematic anxiety level and improve their learning outcomes by applying the Brain Based Learning model. This type of research uses Classroom Action Research which consists of 2 cycles, namely planning, implementation or action, observation or observation, and reflection. The data collection techniques used were interviews, questionnaires, observations, tests, and documentation. The results of this study prove a decrease in students' mathematics anxiety, where in cycle I 10 students experienced high anxiety, while in cycle II there were no students who experienced high anxiety. In addition, student learning outcomes also increased from 63.64% including the sufficient category in cycle I, then in cycle II to 87.88% with a very good category. So this research proves that using the Brain Based Learning model can reduce mathematics anxiety and improve their learning outcomes.